2018
DOI: 10.1016/j.bbi.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Childhood victimization and inflammation in young adulthood: A genetically sensitive cohort study

Abstract: HighlightsChildhood victimization predicted elevated levels of CRP at age 18.The association between child victimization and CRP levels was specific to females.Latent genetic influences on CRP levels did not explain the association in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 56 publications
8
92
2
1
Order By: Relevance
“…Research interest in the ACE–inflammation association is increasing. A recent study on victimisation in childhood and adolescence found associations with inflammatory markers by age 18 in females but not males (Baldwin et al., ). The construct of victimisation overlaps with several of our ACEs including bullying, exposure to domestic violence, physical and sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Research interest in the ACE–inflammation association is increasing. A recent study on victimisation in childhood and adolescence found associations with inflammatory markers by age 18 in females but not males (Baldwin et al., ). The construct of victimisation overlaps with several of our ACEs including bullying, exposure to domestic violence, physical and sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal designs with repeated measures of the pathway investigated are best placed to explicitly test changes over time and account for effects of genetic and prenatal influences, but can be difficult to implement. Genetically sensitive designs including twins and siblings also offer powerful ways to test for selection for unmeasured background characteristics, and improvements in the performances of polygenetic risk scores are increasingly providing instruments for genetic studies in the general population (Baldwin et al, ; Baldwin et al, ; Pingault et al, ). Finally, analytical methods that can measure and maximise the exchangeability of traumatised and nontraumatised children for measured background characteristics, such as propensity score methods and inverse probability weighting methods, can support causal inference (Agoritsas, Merglen, Shah, O'Donnell, & Guyatt, ; Baldwin et al, ).…”
Section: How?mentioning
confidence: 99%
“…Finally, it is important to study potential sex differences in the link between ACEs and neuroinflammatory biomarkers. Some studies show that women have greater neural and inflammatory responses to early stressors (Baldwin et al, ; Ganguly & Brenhouse, ). Others document no such sex differences in the effect of childhood trauma on adult disease and physiological dysregulation (Baumeister, Akhtar, Ciufolini, Pariante, & Mondelli, ; Campbell, Farmer, Nguyen‐Rodriguez, Walker, & Egede, ).…”
Section: Introductionmentioning
confidence: 99%
“…Though ACEs are known to affect neuroinflammatory pathways and health, some research has documented potential sex differences (Baldwin et al, ; Baumeister et al, ). A review article using mammalian models indicates that females generally have greater susceptibility to the inflammatory and neuroendocrine effects of early stress (Ganguly & Brenhouse, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation